PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 16 KUALA PENASO - Rohani, Siti; Erlisnawati, Erlisnawati; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the student achievement of social studies fifth graderes SDN 16 Kuala Penaso still low with an average value of 55,25 and minimum completenness criteria (KKM) social studies is 65. Between students, amounting to 30 people only 10 students who achieve classical KKM with 33,33%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of cooperative learning model type kooperatif tipe Student Team Achievement Division (STAD) can improve students achievment of social studies at SDN 16 Kuala Penaso. The research was conducted on march 11, 2015 to march 20, 2015by 2 cyclees. Subjects were students of SDN 16 Kuala Penaso, totalling 30 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models obtained results koopertif STAD type of activity the teacher in the lerning process in cycle I frist meeting was 66,66% and at the second meeting of teacher activity increased by 12,5% to 79,16%. cycle II firs meeting and the second meeting of activity increased by 4,17% to 83,33% and the second meeting of activity increased by 7,83% to 91,16%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 62,5% and at second meeting of activity increased 12,5% to 75% and a second meeting of activity increased 16,7% improve to 87,5%. At the firs meeting of the second meeting of activity increased 7,5% to 95%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 58. In the first cycle improve an average of 73,33 with increase as 27,29% and an impove in the second with an average of 86,66 with increase as 40,22%. Result in the research that the implementation of cooperative learning model of Student Team Achievement Division (STAD) can improve students achievement of social Studies at fifth graderes SDN 16 Kuala Penaso.Key Words : Model Learning Student Team Achievement Division (STAD), Fave graderes students Achievement